PROTECTIVE EFFECT OF LIGNOCAINE AGAINST ACETYLCHOLINE AND BRADYKININ INDUCED TRACHEAL TISSUE CONTRACTION - Fatima Qasim Malik (Army Medical College Rawalpindi, 2019)
Objective: To evaluate the protective effect of lignocaine against acetylcholine and bradykinin induced airway contraction of isolated tracheal tissue of guinea pig in vitro.